1996
DOI: 10.1044/0161-1461.2703.195
|View full text |Cite
|
Sign up to set email alerts
|

Social Skills of Children With Specific Language Impairment

Abstract: The social skills of 19 elementary school children with specific language impairment (SLI) and 19 chronological age-matched peers were examined. Children in both groups were selected from those children between the ages of 8 and 12 years. Each child with SLI was individually matched to a classmate of the same age. First, the Social Skills Rating System-Teacher Form (Gresham & Elliott, 1990) was administered to provide a general measure of social skill. Following this measure, the quantity of peer relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
87
1
8

Year Published

1998
1998
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(101 citation statements)
references
References 16 publications
3
87
1
8
Order By: Relevance
“…Opportunities for increased and successful social interactions are strongly correlated with the achievement of communicative competence (Prizant, Wetherby, Rubin, & Laurant, 2003). Research indicates that limited communication skills are strongly associated with peer rejection for children with ASD in inclusive classroom settings (Fujiki & Brinton, 1996;Humphrey, 2008;Walker & Berthelsen, 2008). A universally designed classroom is one which provides options for language, optimizes access to assistive technologies and fosters collaboration and community (CAST 2011).…”
Section: Developing Effective Communicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Opportunities for increased and successful social interactions are strongly correlated with the achievement of communicative competence (Prizant, Wetherby, Rubin, & Laurant, 2003). Research indicates that limited communication skills are strongly associated with peer rejection for children with ASD in inclusive classroom settings (Fujiki & Brinton, 1996;Humphrey, 2008;Walker & Berthelsen, 2008). A universally designed classroom is one which provides options for language, optimizes access to assistive technologies and fosters collaboration and community (CAST 2011).…”
Section: Developing Effective Communicationmentioning
confidence: 99%
“…Children with ASD often face challenges socializing in general education classroom settings and have trouble interacting with others (Embregts & van Nieuwenhuijzen, 2009;Fujiki & Brinton, 1996;Humphrey, 2008). Inclusive school settings should set the development of social competence as one of their primary goals (Walker & Berthelsen, 2008).…”
Section: Fostering Genuine Relationshipsmentioning
confidence: 99%
“…Young children with SLI are less socially competent and less successful in peer relations (Fujiki et al, 1996;Gertner, Rice, & Hadley, 1994;McCabe, 2005). Older children with SLI demonstrate poor social competence, poor social cognitive knowledge (Conti-Ramsden & Botting, 2004;Marton et al, 2005) and difficulties with particular social skills, including negotiation strategies (Brinton, Fujiki, & Mckee, 1998) and accessing established interactions (Craig & Washington, 1993).…”
Section: Self-esteem Social Behaviors and Slimentioning
confidence: 99%
“…Traditionally, SLI has been studied with a focus on psycholinguistic and cognitive implications (Bishop, 1997), but it is now clear that language difficulties are also associated with social functioning. Recent research has indicated that children and young people with SLI have a range of social difficulties, including poor social competence and poor peer relations (Conti-Ramsden & Botting, 2004;Durkin & Conti-Ramsden, 2007;Fujiki, Brinton, & Todd, 1996). Young people with SLI may be at risk for lower self-esteem due to their language difficulties and/or problems in other areas of functioning, particularly social difficulties.…”
mentioning
confidence: 99%
“…This may be attributable, in part, to what has often been previously disregarded in research, social and health-care policy, and educational practices; that is, the way in which adolescents' language and communication skills underlie other aspects of their social and academic performance (cf. Camarata, Hughes and RUM, 1988;Fujiki, Brinton and Todd, 1996;Catts, 1997;Sanger, Hux and Belau, 1997).…”
mentioning
confidence: 99%